Situational Analysis of Early Childhood Education in Pakistan: Challenges and Solutions - Mahek Arshad, Shazia Zamir (JECCE, 2023)
Present paper is aimed to provide a critical inquiry of Early Childhood Education (ECE) in Pakistan. It particularly encompassed the beginning of ECE in Pakistan and move towards present day challenges in this area. Objectives of the study were to analyze the development of early childhood education in Pakistan, to highlight the challenges faced in development of early childhood education in Pakistan and to recommend practical solutions for the development of early childhood education in Pakistan by emphasizing its importance. The study adopted qualitative research design. Data were collected from the recorded facts in form of documentation available on early childhood education. Document Analysis was conducted which includes reports and studies on ECE in Pakistan. It was concluded that at present status of ECE in Pakistan is not up to mark, Pakistan is struggling to cope with the present challenges of poverty, lack of awareness, weakness of policy makers, untrained teachers and budgetary issues. It is recommended that stakeholders including public institutes, NGO’s, private sector, religious scholars and parents may perform their role by collaborating with each other to improve ECE in Pakistan. An independent ECE policy and trained teachers are main ingredients.